Tennessee Williams’s Moviegoers, Or the Neglected Gay Aspects of The Glass Menagerie - Dankó, Krisztina (FOCUS: Papers in English Literary and Cultural Studies, 2024)
In scene 6 of The Glass Menagerie (1945) Amanda, the domineering mother, while talking to Laura, cries out like this, “Why can’t you and your brother be normal people? (279, emphasis added). Her hint is clear as regards Laura, the “unmarried sister, who’s crippled and has no job” (312). But the question arises: what is “abnormal” about Tom Wingfield, the poet-narrator of the play, who is seemingly an ordinary young man however unhappy he is with his job at the warehouse or however trapped he feels in his female-dominated nuclear family.